Suplementação injetável de microminerais e vitaminas na reprodução de fêmeas bovinas Bos indicus sincronizadas à IA em tempo fixo - LUANA GOMES DA SILVA (2023)
SILVA, L. G. Injectable trace minerals and vitamins on reproduction of Bos indicus bovine females synchronized to fixed-time AI. Dissertation - Faculty of Veterinary Medicine and Animal Science, Federal University of Mato Grosso do Sul, Campo Grande, MS, 2023. Objectives: The objectives were: Chapter 1) to carry out a literature review on the use of injectable trace minerals (MMI) and vitamins (A and D) in beef cattle Chapter 2) effects of injectable trace minerals (Cu, Zn) in reproduction and responses of Bos indicus female bovines synchronized to fixed-time AI. Chapter 3) Effects of injectable microminerals (Cu, Zn, Se and Mn) and vitamins (A and E) on reproduction and inflammation responses of Bos indicus females synchronized to fixed-time AI. Material and methods: Chap.2) The animals of all experiments were divided into 2 treatments with subcutaneous injection of 5 Ml/female: saline solution or CuZn solution. In experiment 1, 29 Nellore heifers [body weight (BW) = 368 ± 54.1 kg; BSC = 4.8 ± 0.71] synchronized by 9-day protocol (d-9 to d0). In experiment 2, 1469 Nellore females were used, 871 multiparous, 337 primiparous and 261 heifers synchronized per 11-day protocol (d-11 to d0). Chap.3) The animals of all experiments were divided into 2 treatments with subcutaneous injection of 5 mL/female: saline solution or TMVI solution (injectable minerals Cu, Zn, Se and Mn and vitamins A and E). In experiment 1, 68 multiparous Nelore cows [body weight (BW) = 448 ± 38.1 kg; BSC = 4.52 ± 0.84] synchronized by 9-day protocol (d-9 to d0). In experiment 2, 1470 Nellore females were used, 866 multiparous [BW = 441 ± 44.8 kg; BSC = 4.81 ± 0.66] were managed in 13 groups [67 ± 34 cows/group], 341 primiparous [PN = 407.6 ± 36.8 kg; BSC = 5.04 ± 0.54] were managed in 7 groups [33 ± 23 cows/group] and 263 heifers [weight = 334.5 ± 30.1 kg; BSC = 6.08 ± 0.76] were managed in 3 groups [87 ± 17 heifers/group] synchronized by protocol of 11 days (d-11 to d0). Results: Chap.1 The application of MMI and injectable vitamins is an alternative to improve the immune system, weight gain, reproductive performance and reduce gestational losses in beef cattle; Chap.2) With the application of CuZn in experiment 2, heifers CuZn vs. Salina had higher (P = 0.05) BW on d120, higher estrus score (P = 0.01), mating rate (P = 0.04) on d30 and tended (P = 0.10) to have higher pregnancy rate in low BSC on d30 (1st FTAI). No effect (P ≥ 0.45) was detected on body performance in primiparous beef, but primiparous CuZn vs. Salina had higher estrus score (P = 0.03) and higher mating rate on d30 for high BSC females (P = 0.03), also showing a trend towards higher overall estrus score on d30 (P = 0.05), on d70 (P = 0.08) and higher pregnancy rate in low BSC on d30 (P = 0.09). No effects were detected for body (P ≥ 0.14) and reproductive (P ≥ 0.11) performance in multiparous women. CuZn cows vs. Saline showed higher concentration of plasma Cu (P = 0.008) but not Zn (P = 0.56).; Chap.3) The application of TMVI increased the pregnancy rate in heifers with a body condition score (BCS) < 5 at d 30 (P = 0.05) and tended to increase the pregnancy rate at d 120 (P = 0.10) independent of BSC. In primiparous cows, TMVI tended to increase pregnancy rate at d 30 in cows with BSC < 5 (P = 0.09). In multiparous women, TMVI tended to increase (P = 0.10) Cu concentration at d 0. Conclusions: The application of MMI in cattle at the beginning of the TAI protocol improves weight gain in heifers, reproductive performance of heifers and primiparous, but not affect reproduction in multiparous and did not trigger an inflammatory response. The application of TMVI at the beginning of a time-fixed AI protocol reduced inflammatory responses and improved reproduction parameters, mainly in females with low BSC. Keywords: Cattle. Pregnancy rate. Gestational loss. Injectable mineral. Vitamins